The Proximity of Spirit and the Spirit of Proximity - Egbert, Henrik (Zeitschrift für Balkanologie, 2011)
This paper describes the production of brandy in a small village in the Central Southern Rhodopes in Bulgaria. The production of alcohol has not been included in previous anthropological studies of the region. The paper shows that the making of brandy is not only a collective activity but also contributes to a common identity referring – in this case – to a specific village. The case illustrates a return to the collective, however, this time not organized by the state in the form of a co-operative but privately organized. The production of alcohol may thus be understood as a group activity that gives a meaning other than economic.